Role of Micro-finance & Self-help Groups in Women Empowerment - et al., Tandraleem Kashyap (International Journal of Advanced Science and Technology, 2020)
Women are an integral part of every economy. All round development and harmonious growth of a nationwould be possible only when women are considered as equal partners in progress with men. Microfinance and Self-help groups (SHG) are now proven strategy for reaching poor women. Micro-financeand SHG can empower poor women by providing facilities like savings and credit in the economicdevelopment process of the society. Micro-finance and SHG are means of social empowerment andupliftment of the poor specially women as it helps in increasing standard of living and coming out ofpoverty. The main purpose of such an association is to enable poor women members to gain economicbenefits out of mutual help, solidarity and social responsibility. The present research paper is an attemptto study the role of Micro-finance and SHGs in empowering women.